Olympic Games - Tuakli-Wosornu YA; Moses EC; Amick M; Grimm K (Dynamic Media Sales Verlag, 2021)
Unethical behaviors in sport are a matter of global concern. The current surge in reports on abuse of athletes across sports and all over the world is reminiscent of the doping scandals in the 1980s and 1990s that made many believe that doping was endemic in Sport.This realization eventually led to a concerted effort of sport stakeholders and the founding of the World Anti-Doping Agency, which has since established itself as the worlds governing body in anti-doping with substantial influence and power.Framing the history and trajectory of anti-doping as a precedent of what has worked and what has not in righting sports wrongs, this review asks: what can the two-decades-long anti-doping fight teach us about protecting athletes from abuse? Exploring various aspects from the effectiveness of external regulation and the challenges of a centralized legalistic approach to athlete health protection and accountability, several lessons that have implications for safeguarding athletes can be identified. Behavior change is a long and demanding process for individuals and organizations.Centering athletes voices and lived experiences in practical research approaches while integrating multi-sector stakeholders can help ensure that methods and findings are fit-for-purpose and inform effective, sustainable athlete-safeguarding practices, programs, and policies.Key Words: Dangerous Behavior, Doping in Sports, Interpersonal Relations, Physical Abuse, Sexual Abuse, Psychological Abuse